PENGARUH PARTISIPASI ANGGARAN, KOMITMEN ORGANISASI, DAN BUDGET EMPHASIS TERHADAP BUDGETARY SLACK PADA HOTEL BINTANG 5 DI BADUNG - Ni Putu Selin Viantari; Yogantara, Komang Krishna; Asana, Gde Herry Sugiarto (Journal of Applied Management and Accounting Science, 2024)
The budget is a tool utilized by companies to regulate resource utilization within a specified timeframe. However, discrepancies frequently arise between the planned budget and actual execution, potentially leading to what is known as budgetary slack. This slack occurs due to conflicts between those setting the budget and those implementing it. Among the factors contributing to budgetary slack are involvement in budgeting, dedication to the organization, and emphasis placed on the budget. This study aims to explore how involvement in budgeting, dedication to the organization, and emphasis on the budget impact budgetary slack within the setting of 5-star hotels in Badung. It adopts a quantitative approach, with the population consisting of 65 5-star hotels in Badung. The sample comprises 220 respondents selected through non-probability sampling, specifically use ipurposive isampling. Multiple linear regressiont ianalysis is utilized for data ianalysis. The findings reveal that both involvement in budgeting and emphasis on the budget positively affect ibudgetary slack in 5-star hotels in Badung. Conversely, dedication to the organization demonstrates a negative correlation with budgetary slack in the same context. The combined influence of involvement in budgeting, dedication to organization, and emphasis on the budget accounts for 44.5% of the variability in budgetary slack, while the remaining 55.5% is attributed to external variable not addressed in this study.